Marsupial Sue - Lithgow, John, 1945-; Davis, Jack E. (New York : Simon & Schuster Books for Young Readers, 2001)
Marsupial Sue, a young kangaroo, finds happiness in doing what kangaroos do.
NP
Accelerated Reader AR
Keywords: Kangaroos -- Fiction; Identity -- Fiction; Stories in rhyme